Geology and genesis of the cerro la mina porphyry-high sulfidation Au (Cu-Mo) prospect, Mexico - Jansen, N.; Gemmell, J.; Chang, Z.; Cooke, D.; Jourdan, Fred; Creaser, R.; Hollings, P. (Society of Economic Geologists Inc, 2017)
The Cerro la Mina Au (Cu-Mo) porphyry-high sulfidation prospect is located in Chiapas State, southeastern Mexico, outside of the major metallogenic provinces of Mexico. The prospect is hosted by Pleistocene alkaline volcanic rocks of the Chiapanecan volcanic arc that formed in a complex triple-junction tectonic setting. Cerro la Mina's stratigraphy comprises pyroclastic flows that were intruded by monzodiorites and diorites at 1.04 ± 0.04 Ma (U-Pb, zircon), and that were overlain by debris flows and synvolcanic trachyandesite domes. The volcanic stratigraphy of Cerro la Mina is dominated by pyroclastic flows and rare basalts that are cut by the Cerro la Mina breccia pipe, a matrix-rich granular, vertically oriented, downward-Tapering, polymict lithic rock unit that is host to all of the significant alteration and mineralization. A NW-Trending sinistral wrench fault, which was active throughout the history of Cerro la Mina, is responsible for dismembering the prospect after mineralization. The magmatic hydrothermal system was composed of early porphyry-style potassic veins (quartz + K-feldspar ± biotite) and stage 1 pyrite that are preserved in clasts within the breccia pipe, suggesting that brecciation disrupted an embryonic porphyry system. Late potassic alteration occurred after the formation of the breccia pipe, as its matrix is strongly K-feldspar altered. Hydrothermal fluids then produced phyllic alteration composed of quartz, muscovite, illite, illite-smectite, and chlorite that is associated with stage 2 pyrite ± chalcopyrite ± molybdenite ± quartz veins. An unusual zoned pattern of advanced argillic-Argillic alteration overprinted potassic and phyllic alteration. This zoning included a low-Temperature (<110°C) halloysite + kaolinite that extends from 800 to 250 m below present-day surface and is deeper than higher temperature (>120°C) quartz + dickite ± kaolinite ± pyrophyllite ± alunite that occurs from 250 m to the present-day surface. The advanced argillic-Argillic altered rocks host the most significant Au-Cu mineralization, which is associated with stage 3 marcasite, sphalerite, galena, and barite, and stage 4 arsenian pyrite ± enargite ± covellite. The magmatic hydrothermal system at Cerro la Mina began sometime between monzodiorite emplacement (1.04 ± 0.04 Ma; zircon U-Pb) and the precipitation of porphyry stage 2 molybdenite at 780 ± 10 ka (Re-Os). 40Ar/39Ar dating of biotite (689 ± 13 ka) records the age at which the hydrothermal system cooled below the biotite closure temperature of 300°C and provides a maximum estimate for the onset of advanced argillicargillic alteration. Sulfur isotope results of sulfides (-2.5 to +4.9‰; mean +0.7‰; n = 20) and a sulfate (barite; +10.5‰; n = 1) suggest a magmatic source of sulfur for all four stages of mineralization. The lack of residual quartz, rare alunite, and anomalous halloysite-kaolinite alteration may be explained by the high acid-buffering capacity of alkaline volcanic host rocks, high CO2 contents of the alkaline magma, and/or potentially by a highly reduced magmatic hydrothermal fluid. At the regional metallogenic scale, the Cerro la Mina prospect along with the nearby Santa Fé mine and Campamento deposit represent parts of a porphyry copper system-specifically, a porphyry/high-sulfidation, proximal skarn and intermediate sulfidation deposit, respectively. The characteristics of Cerro la Mina (i.e., anomalous halloysite-kaolinite alteration) broaden the window for additional discoveries to be made in the porphyry-epithermal environment.